Analisa Pengaruh Bentuk Saluran Pendingin Terhadap Cacat Warpage dari Produk Injeksi Plastik Berbahan Polypropylene - Priyanto, Priyanto (2016)
Injection molding is a plastic forming process by way of melting the plastic material is injected into a mold (mold). Defects that often occur in injection molding products include a short shot (defective products less full), Sink mark (point defects such as concave on the product) flash (excess material defect at the edge of the product) and warpage (arch defects in the product). The causes of warpage is affected by the injection pressure, mold temperature, melting and holding time in the injection process (Huang and Tai, 2001). Therefore, the aim of this study was to investigate the effect of the defective form of cooling channels warpage of the results of injection molding products and to determine the exact shape of the cooling channels to obtain the optimal product of injection molding. The initial step of making the mold (mold) with a CNC milling machine and manufacturing of coolers with soft tooling system type of conformal cooling channels and cooling type straight line. Sooftoling system is made by mixing powdered aluminum and epoxy glue in the ratio 2: 1 channel conformal printed therein. The data collection method extents used image processing with image capture using the camera 14 pixel and processed using software solidwork so it can be analyzed statistically and for measuring cup (point arch top) used a dial indicator, after we got the result, niali warpage can be determined by (cup : diameter = warpage) can then be drawn to a conclusion. From the results of the study concluded that in this study the general area of greatest warpage occurs in the form of a straight cooling channel with an average of 5724,71mm and warpage smallest area to form conformal cooling channel with an average of 4427,49mm. As for the value that most large warpage occurs in the form of the conformal cooling channels, namely with an average of 0.0452 and the smallest value of warpage occurs in the form of straight cooling channel that is with an average of 0.0375. Keywords: injection molding, solidwork, dial indicator, coolant channels form, warpage